Se former à l’usage des dispositifs de téléprésence, visioconférence et webconférence en enseignement supérieur: - Bolduc, Simon; Petit, Matthieu; Meyer, Florian; Bédard, Denis; Challah, Rana (Médiations et médiatisations, 2020)
Technopedagogical devices such as video conferencing are emerging technologies that are increasingly in use in higher education. Some educational institutions invest heavily in their implementation and deployment for distance learning education. However, little is known about the uses that trainers make of them and about the role of educational advisors in this context. This paper presents a study carried out as part of the TOPIC project (Téléprésence comme OPportunité d’Innovation dans la Conception de formation) a joint project between the University of Sherbrooke (Canada) and the Université Bretagne Loire (France). An online survey was sent to 174 trainers from the two partner universities using the following questions "What are the current uses, the level of ease and the expectations of teachers vis-à-vis technopedagogical (videoconference) devices? ". Survey findings show that video conferencing devices are not widely used, that there is little use of videoconferencing devices, and that trainers are poorly trained (or receive little training) to use them. Nevertheless, a majority of respondents to the online survey indicated that they were confident in their ability to teach using digital technology. In terms of training, the online survey findings show that trainers favour the use of self-training resources, personalized accompaniment support or a combination of resources and support.
Number: 3
Keywords: conseiller pédagogique; dispositif technopédagogique; développement professionnel; enseignement supérieur; formation continue; téléprésence; visioconférence; webconférence